Mechanism of umbilical cord mesenchymal stem cells in the expansion of umbilical cord blood-derived hematopoietic stem cells in vitro - Zhuo-yang Bian; Li Xu (Journal of International Medical Research)
The methodologies and applications of ex vivo expansion of umbilical cord blood cells represent a significant research domain, primarily owing to the distinctive characteristics of these cells and their prospective uses in regenerative medicine and hematopoietic stem cell transplantation. We searched PubMed and Web of Science using the terms “umbilical cord blood cells,” “cytokine,” “haematopoietic cells,” “umbilical cord mesenchymal stem cells,” “in vitro expansion,” and “microenvironment,” and the selected literature was organized and analyzed. We present a narrative review of the mechanisms by which umbilical cord mesenchymal stem cells enhance the in vitro expansion of umbilical cord blood-derived hematopoietic stem cells, focusing on three primary aspects: secretion of diverse cytokines to replicate the natural hematopoietic microenvironment, transmission of critical signals via direct cell-to-cell contact, and exertion of immunomodulatory effects to alleviate environmental stress. Although these processes can significantly promote the proliferation and survival of hematopoietic stem cells, the challenge of concurrently preserving the long-term stemness of these cells in an in vitro environment remains a critical issue for future research.